AN ANALYSIS OF FACTORS INFLUENCING THE DECISIONS OF BEKASI PEOPLE TO ENDOW CASH WAQF - Nastiti, Hasna Mumtaz; Anggraini, Ika Khusnia (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
Muslims are encouraged to seek Allah's blessings and help each other in need, which can be done by setting aside a portion of the wealth for waqf. Waqf is one of the instruments of Islamic philanthropy oriented towards sustainable benefits to improve people's welfare. The object of waqf was originally in the form of fixed assets, now experiencing development with the provision of collective cash waqf for development. The ease of this method makes the potential large enough in its collection. However, the current realization of cash waqf is not as big as the existing potential, around billions of rupiah, while the potential for waqf reaches trillions of rupiah. With several variables found, this study aims to determine the effect of each independent variable, namely cash waqf literacy, income, Ihsan, and Islamic egalitarianism, on the cash waqf decisions of the Bekasi community. The research was conducted in the Bekasi area because cash waqf was developing. The method used is descriptive quantitative with a logistic regression analysis tool. The result of this study is only cash waqf literacy significantly affects the Bekasi community's decision in cash waqf because individuals with knowledge of cash waqf have a greater chance of cash waqf.